Probing the prodigious strain fringes from Lourdes. (December 2017) - Aerden, Domingo G.A.M.; Sayab, Mohammad
Abstract: We investigate the kinematics of classic sigmoidal strain fringes from Lourdes (France) and review previous genetic models, strain methods and strain rates for these microstructures. Displacement controlled quartz and calcite fibers within the fringes yield an average strain of 195% with the technique of Ramsay and Huber (1983). This agrees well with strains measured from boudinaged pyrite layers and calcite veins in the same rocks, but conflicts with ca. ∼675% strain in previous analogue models for the studied strain fringes produced by progressive simple shear. We show that the detailed geometry and orientation of fiber patterns are insufficiently explained by simple shear but imply two successive, differently oriented strain fields. Although all strain fringes have the same overall asymmetry, considerable morphological variation resulted from different amounts of rotation of pyrite grains and fringes. Minor rotation led to sharply kinked fibers that record a ca. 70° rotation of the kinematic frame. Larger (up to 145°) rotations, accommodated by antithetic sliding on pyrite-fringe contacts, produced more strongly and smoothly curved fibers. Combined with published Rb-Sr ages for the studied microstructures, our new strain data indicate an average strain rate of 1.41 10 −15 s −1 during ca. 37 Myr. continuous growth. Graphical abstract: Highlights: Different kinematics models for classic strain fringes from Lourdes are tested against quantitative data for fiber geometry and matrix strain. The Lourdes strain fringes record a superposition of two deformation phases with differently oriented kinematic axes. Combined with previous radiometric ages for strain fringe increments, our data indicate an average strain rate of 1.41 10 −15 /s or 4.5%/Myr during ca. 37 Myr of continuous growth.